Razvitie vynoslivosti u kon'kobežcev 16-18 let interval'nym metodom - Tretyakov, A. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article presents a study of increasing the level of endurance development of 16-18-year skaters with interval training method. To carry out an experiment we chose two groups of speed skaters in Specialized Children and Youth Sports School of the Olympic Reserve of speedskating who did not have any significant differences in indicators under the study. We proposed our methodology of endurance development for the experimental group. At the beginning and in the end of the experiment we conducted control tests. At the end of the experiment in the same conditions and also after a rest-day control tests were conducted. For comparison of results of the study we chose functional tests of cardiovascular system, which can be undertaken in standard (or laboratory) conditions: PWC 170 test and Harvard step test (IGST). The control group was training according generally accepted methodology of the Specialized Children and Youth Sports School of the Olympic Reserve. The experimental group was training according the following method. We proposed two mesocycle workouts based on two weekly microcycles: microcycle aimed at development of special endurance at the stage of special physical training; microcycle using training on the ice at the stage of special training. According to the results of research using interval method with the designed complexes allowed significantly increase the level of endurance development within the shortest time period (8 weeks).